Acyl-ghrelin Is Permissive for the Normal Counterregulatory Response to Insulin-Induced Hypoglycemia - Shankar, Kripa (Diabetes, 2020)
Insulin-induced hypoglycemia leads to far-ranging negative consequences in patients with diabetes. Components of the counterregulatory response (CRR) system that help minimize and reverse hypoglycemia and coordination between those components are well studied but not yet fully characterized. Here, we tested the hypothesis that acyl-ghrelin, a hormone that defends against hypoglycemia in a preclinical starvation model, is permissive for the normal CRR to insulin-induced hypoglycemia. Ghrelin knockout (KO) mice and wild-type (WT) littermates underwent an insulin bolus-induced hypoglycemia test and a low-dose hyperinsulinemic-hypoglycemic clamp procedure. Clamps also were performed in ghrelin-KO mice and C57BL/6N mice administered the growth hormone secretagogue receptor agonist HM01 or vehicle. Results show that hypoglycemia, as induced by an insulin bolus, was more pronounced and prolonged in ghrelin-KO mice, supporting previous studies suggesting increased insulin sensitivity upon ghrelin deletion. Furthermore, during hyperinsulinemic-hypoglycemic clamps, ghrelin-KO mice required a 10-fold higher glucose infusion rate (GIR) and exhibited less robust corticosterone and growth hormone responses. Conversely, HM01 administration, which reduced the GIR required by ghrelin-KO mice during the clamps, increased plasma corticosterone and growth hormone. Thus, our data suggest that endogenously produced acyl-ghrelin not only influences insulin sensitivity but also is permissive for the normal CRR to insulin-induced hypoglycemia.